(untitled) (Jurnal Edukasi dan Penelitian Matematika, 2025)
Mathematical concept understanding is a fundamental skill that students must acquire before mastering other mathematical abilities. However, at MTsN 6 Kota Padang, students’ understanding of mathematical concepts remains relatively low. This study aims to determine whether the Contextual Teaching and Learning (CTL) approach can improve students’ conceptual understanding compared to the scientific approach. This research is a quasi-experimental study using a posttest-only control group design. The population consists of all seventh-grade students at MTsN 6 Kota Padang, with samples selected through simple random sampling. Class VII.2 was designated as the experimental group, and class VII.4 as the control group. Data were collected using a posttest on conceptual understanding and analyzed using the mean difference test. The statistical analysis showed that the average score of the experimental class was higher than that of the control class. Based on the t-test, the result showed a P-value < α, indicating a significant difference between the two groups. Therefore, it can be concluded that learning using the CTL approach is more effective in improving students’ understanding of mathematical concepts compared to the scientific approach.